PENGARUH TEKNIK PENYIMPANAN TERHADAP PENGENDALIAN AFLATOKSIN JAGUNG (Zea mays L) SELAMA PENYIMPANAN - Hasnani S Hasnani S; Jamaluddin Jamaluddin; Ratnawaty Fadilah (Jurnal Pendidikan Teknologi Pertanian, 2022)
The purpose of this study was to determine the method of controlling the levels of aflatoxin corn with storage techniques using plastic sack packaging without base and with pedestal during storage. This research method is in the form of an experiment using a T test with 2 treatments repeated three times. The treatment in this study is shelled corn packaging plastic sacks without base and shelled corn packaging plastic bag with a base. During storage the sample is observed levels of aflatoxin, water content, air humidity and temperature. The results showed that there were differences in levels of aflatoxin and increased with the length of storage. The best treatment is obtained from the shelled corn using a base at 7th day, 14th day, 21st and 28th day storage with an average value of 32.33 ppb, 36.66 ppb, 44 ppb and 49 ppb. Analysis of the levels of aflatoxin in the treatment of piped corn packing plastic bags using a base meets the requirements of corn quality based on Indonesian National Standards.